Effects of exercise of different intensities on withdrawal symptoms among people with substance use disorder: a systematic review and meta-analysis - Li, Hao; Su, Wantang; Cai, Jiajia; Zhao, Li; Li, Yan (Frontiers in Physiology, 2023)
Exercise can effectively attenuate withdrawal symptoms and reduce relapse, but whether different exercise intensities show divers results is unknown. This research aims to systematically review the effects of different exercise intensities on the withdrawal symptoms among people with substance use disorder (SUD). Randomized controlled trials (RCTs) about exercise, SUD and abstinent symptoms were systematically searched using electronic databases including PubMed et al. up to June 2022. The assessment of study quality was evaluated by the Cochrane risk of bias (ROB) tool. The meta-analysis was performed by calculating the standard mean difference (SMD) of outcomes from light, moderate and high exercise intensities in the individual studies with the Review Manager version 5.3 (RevMan 5.3). 22 RCTs (n=1537) were included. Overall, exercise interventions had significant effects on the withdraw symptoms, but the effect size varied from different exercise intensities and different negative emotion outcomes. Light, moderate and high intensity exercises reduced craving after the interventions [SMD=-0.69, 95%CI=(-0.88, -0.49)], and there was no statistical differences between the subgroups (P>0.05). Light, moderate and high intensity exercise reduced depression after the interventions [light, SMD=-0.33, 95%CI=(-0.57, -0.09); moderate, SMD=-0.64, 95%CI=(-0.85, -0.42); high, SMD=-0.25, 95%CI=(-0.44, -0.05)], and moderate intensity exercise showed the best effect (P<0.05). Only light and moderate intensity exercises relaxed the anxiety after the interventions [low, SMD=-0.51, 95%CI=(-0.74, -0.29); moderate, SMD=-0.58, 95%CI=(-0.85, -0.31)]. Only high intensity exercise worked in stress alleviation [SMD=-1.13, 95%CI=(-2.22, -0.04)]. Both irritability and restless could be improved by light and moderate intensity exercises [light, SMD=-0.75, 95%CI=(-0.99, -0.51); moderate, SMD=-0.71, 95%CI=(-0.96, -0.45)], and there was no statistical differences between the subgroups (P>0.05). Moderate and high intensity exercises decreased withdrawal syndromes after the interventions [moderate, SMD=-0.33, 95%CI=(-0.61, -0.05); high, SMD=-1.33, 95%CI=(-1.90, -0.76)], high intensity exercise showed the best effect (P<0.01). Exercise leads to improvements on the withdrawal symptoms in individuals with SUD, but these effects are significantly different between the exercise intensities and the type of withdraw symptoms. Moderate intensity exercise has the greatest benefits in improving depression and anxiety. High intensity exercise has the greatest benefits in improving stress and syndrome.